2020
DOI: 10.1002/adfm.201909114
|View full text |Cite
|
Sign up to set email alerts
|

Optically Modulated Threshold Switching in Core–Shell Quantum Dot Based Memristive Device

Abstract: The threshold switching (TS) phenomenon in memristors has drawn great attention for its versatile applications in selectors, artificial neurons, true random number generators, and electronic integrations. The transition between nonvolatile resistive switching and volatile TS modes can be realized by doping, varying annealing and voltage sweeping conditions, or imposing different compliance current. Here, a strategy is reported to achieve such transition by the noninvasive UV light stimulus based on InP/ZnS qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 83 publications
0
66
0
Order By: Relevance
“… (I) Integration-and-fire behavior emulated by InP/ZnS-based memristor. Reproduced with permission ( Wang et al., 2020 ). Copyright 2020, John Wiley & Sons, Inc. …”
Section: Artificial Neurons Based On Emerging Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“… (I) Integration-and-fire behavior emulated by InP/ZnS-based memristor. Reproduced with permission ( Wang et al., 2020 ). Copyright 2020, John Wiley & Sons, Inc. …”
Section: Artificial Neurons Based On Emerging Materialsmentioning
confidence: 99%
“…In addition, memristors have also been used to realize the integrate-and-fire model of neuron by optical modulation. An artificial neuron was fabricated using core-shell quantum dots (QDs) composed of InP core and ZnS shell ( Wang et al., 2020 ). A device that had Ag/(InP/ZnS) QDs/ITO structure showed non-volatile resistive switching behavior under a dark condition, but showed threshold switching behavior under UV illumination ( Figure 10 G).…”
Section: Artificial Neurons Based On Emerging Materialsmentioning
confidence: 99%
“…The following describes a recent study on changes in switching types by analyzing peripheral charges of CFs inside films. Wang et al ( 2020 ) reported an analysis using KPFM on instant changes between threshold switching and resistive switching during UV irradiation of films with InP/ZnS quantum dot-based memristive devices. There is a quantum dot-based switching layer between Ag and ITO electrodes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…InP/ZnS quantum dots (QDs)-based memristor; the memristive mode of the device can be transited from nonvolatile resistive switching to volatile TS under UV illumination. [61] In this work, the designed visual neuron based on LIF model was implemented on InP/ZnS QD-based memristor (Figure 6b). During the experiment, the memristor showed TS behavior UV illumination.…”
Section: Volatile Memristor As Artificial Neuronmentioning
confidence: 99%